Amino‐Terephthalonitrile‐Based Single Benzene Fluorophores with Large Stokes Shifts and Solvatochromic Behavior. Issue 8 (9th March 2023) - Raghava, Tanya; Chattopadhyay, Anjan; Bhavana, Purushothaman; Banerjee, Subhadeep
Abstract: We have synthesized a small library of blue‐to‐green emissive single benzene‐based fluorophores (SBFs) in a short synthetic sequence. The molecules exhibit good Stokes shift in the range of 60–110 nm and select examples also possess very high fluorescence quantum yields of up to 87%. Theoretical investigations into the ground state and excited state geometries of many of these compounds reveal that good degree of planarization between the electron donor secondary amines and electron accepting benzodinitrile units can be achieved under certain solvatochromic conditions, giving rise to the strongly fluorescent behavior. On the other hand, the excited state geometry which lacks co‐planarity of the donor amine and the single benzene moiety can open up a non‐fluorescent channel. Additionally, in molecules with a dinitrobenzene acceptor, the perpendicular nitro moieties render the molecules completely non‐emissive. Abstract : Single benzene fluorophores (SBFs) containing secondary and or tertiary amines and the terephthalonitrile moiety in direct conjugation with each other across a benzene ring, were synthesized and their emissive character were investigated using theoretical and experimental methods. Results show that there is a strong interplay between molecular geometry and the push‐pull type charge delocalization in rendering the SBFs strongly emissive.